The influence of hip joint rotation of a physical assistant robot on curving motion. (17th January 2021) - Kuboki, Yosuke; Akiyama, Yasuhiro; Okamoto, Shogo; Yamada, Yoji
ABSTRACT: The use of physical assistant robots is expanding to activities of daily living. However, the risk of a user falling which can occur in various environments has not yet been considered despite this being a major concern for such robots. Therefore, this study focuses on curving motion, during which falling is more likely to occur, especially when the degree of freedom of the hip joint is restricted by the robot. We developed a physical assistant robot with an adjustable degree of freedom of hip rotation and observed the curving motions of the wearer under different joint restriction conditions. The result was statistically tested and the characteristics were extracted using factor analysis. It was noted that in the trials involving the restriction of hip rotation, the step length, pelvis yaw angle, and speed were significantly decreased with the decrease in hip rotation. However, as the participants changed their curving motion to compensate for the effect of joint restriction, the margin of stability varied slightly. This result suggested the necessity of implementing an assist algorithm that could change the gait motion to compensate and improve gait stability when curving. GRAPHICAL ABSTRACT: UF0001